2018
DOI: 10.1093/scan/nsy103
|View full text |Cite
|
Sign up to set email alerts
|

Learning to see the threat: temporal dynamics of ERPs of motivated attention in fear conditioning

Abstract: Social threat detection is important in everyday life. Studies of cortical activity have shown that event-related potentials (ERPs) of motivated attention are modulated during fear conditioning. The time course of motivated attention in learning and extinction of fear is, however, still largely unknown. We aimed to study temporal dynamics of learning processes in classical fear conditioning to social cues (neutral faces) by selecting an experimental setup that produces large effects on well-studied ERP compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…The finding that fear-conditioned neural evoked responses were reflected in a larger SPN probably indicates expectation and possible preparatory processes similar to flight-or-fight responses. An analogous increased SPN waveform has been shown to be predictive of emotionally charged events (Baas et al, 2002 ; Böcker et al, 2001 ; Dahl et al, 2020 ; Ferreira de Sá et al, 2019 ; Hellwig et al, 2008 ; Regan & Howard, 1995 ), whereas anticipatory attention to stimuli with no motivational value elicited reduced SPN (Brunia et al, 2011 ). This interpretation is in line with the observation that in the present study the SPN amplitude to the CS+ was generally larger in 100% reinforcement trials than in 50% reinforcement trials, whereas the responses to the US were weaker in 100% than 50% reinforcement trials.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The finding that fear-conditioned neural evoked responses were reflected in a larger SPN probably indicates expectation and possible preparatory processes similar to flight-or-fight responses. An analogous increased SPN waveform has been shown to be predictive of emotionally charged events (Baas et al, 2002 ; Böcker et al, 2001 ; Dahl et al, 2020 ; Ferreira de Sá et al, 2019 ; Hellwig et al, 2008 ; Regan & Howard, 1995 ), whereas anticipatory attention to stimuli with no motivational value elicited reduced SPN (Brunia et al, 2011 ). This interpretation is in line with the observation that in the present study the SPN amplitude to the CS+ was generally larger in 100% reinforcement trials than in 50% reinforcement trials, whereas the responses to the US were weaker in 100% than 50% reinforcement trials.…”
Section: Discussionmentioning
confidence: 92%
“…Previous fear conditioning research employing EEG identified several ERP components that may serve as indices of conditioned responses. ERP components, such as P1 (Pizzagalli et al, 2003 ), N1 or P2 (Kluge et al, 2011 ), and P3 (Kotchoubey & Pavlov, 2017 ; Pavlov & Kotchoubey, 2019 ; Rothemund et al, 2012 ), the LPP (Bacigalupo & Luck, 2018 ; Panitz et al, 2015 ; Pavlov & Kotchoubey, 2019 ; Sperl et al, 2021 ), and the SPN (Baas et al, 2002 ; Böcker et al, 2001 ; Ferreira de Sá et al, 2019 ; Hellwig et al, 2008 ; Regan & Howard, 1995 ), have been reported to produce a differential response in the contrast between conditioned stimuli (CS+) and safety signals (CS−). The processes manifested in these different ERP components can help to unveil the mechanisms underlying the consolidation of fear memories.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that fear-conditioned neural evoked responses were reflected in a larger SPN probably indicates expectation and possible preparatory processes similar to flight or fight responses. An analogous increased SPN waveform has been shown to be predictive of emotionally charged events (Baas et al, 2002; Böcker et al, 2001; Dahl et al, 2020; Ferreira de Sá et al, 2019; Hellwig et al, 2008; Regan & Howard, 1995), while anticipatory attention to stimuli with no motivational value elicited reduced SPN (Brunia et al, 2011). This interpretation is in line with the observation that in the present study the SPN amplitude to the CS+ was generally larger in 100% reinforcement trials than in 50% reinforcement trials, whereas the responses to the US were weaker in 100% than 50% reinforcement trials.…”
Section: Discussionmentioning
confidence: 94%
“…a slow ERP component that typically appears after 400 ms with a maximum at the posterior electrodes, is a particularly reliable conditioning index (Bacigalupo & Luck, 2018; Panitz et al, 2015; Pavlov & Kotchoubey, 2019; Sperl et al, 2021). Other studies found the stimulus preceding negativity (SPN), i.e., a slow ERP component that typically occurs between 200 and 500 ms before the presentation of emotionally relevant stimuli (Ferreira de Sá et al, 2019; Tanovic et al, 2018; Tanovic & Joormann, 2019), to be a suitable conditioning index by showing a greater amplitude to cues predicting threat than safety events (Baas et al, 2002; Böcker et al, 2001; Ferreira de Sá et al, 2019; Hellwig et al, 2008; Regan & Howard, 1995). The earlier ERP components, such as P1, N1, and P2, can manifest changes in sensory processing of conditioned stimuli (Miskovic & Keil, 2012), while P3 may represent attention capture (Pavlov & Kotchoubey, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation